2019
DOI: 10.3906/biy-1909-31
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 inflammasome: a new player in neurological diseases

Abstract: Inflammasomes are supramolecular protein complexes implicated in the detection of pathogens or danger-associated molecules and are responsible for mounting the first line of innate immune response to counteract these signals and restore tissue homeostasis. Among different inflammasomes identified so far, NLRP3 is of main interest since mutations in Nlrp3 gene are associated with autoinflammatory diseases such as Muckle–Wells syndrome, neonatal onset multisystem inflammatory disease, and familial cold urticaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…As a component of pyroptosis, NLRP3 inflammasome is of concern because it can be activated by various PAMPs and DAMPs and it is closely related to various human diseases (Gong et al, 2018 ; Liu et al, 2018 ; Eren and Özõren, 2019 ). When NLRP3 is assembled and activated, caspase-1 can be activated and turn pro-IL-1β and GSDMD into the bioactive cytokines IL-1β and GSDMD-N, respectively (Hou et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a component of pyroptosis, NLRP3 inflammasome is of concern because it can be activated by various PAMPs and DAMPs and it is closely related to various human diseases (Gong et al, 2018 ; Liu et al, 2018 ; Eren and Özõren, 2019 ). When NLRP3 is assembled and activated, caspase-1 can be activated and turn pro-IL-1β and GSDMD into the bioactive cytokines IL-1β and GSDMD-N, respectively (Hou et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This effect was similar to the NLRP3 inhibitor MCC950 and was reversed by NLRP3 overexpression. Various studies have found that ROS represents a key signal that regulates the activation of the NLRP3 inflammasome (Tschopp and Schroder, 2010 ; Eren and Özõren, 2019 ). We found that the ROS level in the cells subjected to OGD/R was increased significantly and that BMSC-Exos could weaken this response, indicating that BMSC-Exos reduced pyroptosis mediated by the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…The NOD-like receptor (NLR) is a pattern recognition receptor (PRR) family member, and these receptors are found in the cytosol and are able to identify pathogen-associated molecular patterns (PAMPs) and damage associated molecular patterns (DAMPS) ( Adachi and Tsuda, 2019 ). NLRP3 is the most studied member in the NLR family, and it is expressed in granulocytes, monocytes, dendritic cells, T cells, and epithelial cells ( Eren and Özören, 2019 ). The NLPR3 inflammasome consists of the NLRP3 receptor, the adaptor apoptosis-associated speck-like protein containing a CARD (ASC), and the effector cysteinyl aspartate specific proteinase (caspase-1).…”
Section: Introductionmentioning
confidence: 99%
“…Literature suggest that NLRP3 has a proven role in the neuronal dysfunction by enhancing the apoptosis through the activation of caspase pathway and NLRP3 inflammasome pathway reported to be involved in CPB surgery induced brain injury (Eren and Özören, 2019). ROS also contributes in the development of neuronal injury by regulating NLRP3 pathway (Abais et al, 2015).…”
Section: Discussionmentioning
confidence: 99%